Managing Universiti Sains Malaysia libraries 2.0: developing strategic leadership values for librarians - Ghadzali, Mohd Pisol; Mohamad, Radia Banu Jan Mohamad; Misaridin , Shahriza Fadly (2008)
Leadership plays a very important role in managing an academic Library 2.0. Leaders must be provided with opportunities to learn manage libraries successfully congruent with the rapid changes in technologies. Future leaders must develop competencies and they should also have some familiarity with ways of developing competencies for dealing with the broad, new challenges that are part of leading in the strategic environment.